2022
DOI: 10.1155/2022/6447471
|View full text |Cite
|
Sign up to set email alerts
|

Research on Methods of Physical Aided Education Based on Deep Learning

Abstract: In order to better meet the training needs of sports and improve the standardization of sports training, an openpose-based sports posture estimation method and assisted training system are proposed, combining the basic structure and principle of openpose network. Firstly, the human posture estimation algorithm is constructed by combining with the openpose network; secondly, the overall framework, specific operation process, image acquisition, posture estimation, and other modules of the sports assistance syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the algorithm exhibits poor robustness and struggles to cope with the challenges of complex human pose estimation in current scenarios. Su et al [9] (2022) proposed a motion pose estimation algorithm based on OpenPose and trained it using the COCO dataset. Through comparison with standard poses, the study demonstrated the algorithm's ability to accurately recognize various badminton action poses, with a recognition rate of up to 94%.…”
Section: Contribution Of This Articlementioning
confidence: 99%
“…However, the algorithm exhibits poor robustness and struggles to cope with the challenges of complex human pose estimation in current scenarios. Su et al [9] (2022) proposed a motion pose estimation algorithm based on OpenPose and trained it using the COCO dataset. Through comparison with standard poses, the study demonstrated the algorithm's ability to accurately recognize various badminton action poses, with a recognition rate of up to 94%.…”
Section: Contribution Of This Articlementioning
confidence: 99%